ASSESSING THE VALIDITY AND RELIABILITY OF THE TURKISH VERSION OF THE MATE RETENTION INVENTORY - SHORT FORM - Wise, Ryan Macey; Karkılı, Senanur (Tuncay AYDEMİR, 2022)
The current study examined the psychometric features of the Turkish translation of the Mate Retention InventoryShort Form (MRI-SF) in Turkey. For this study, 286 participants were recruited with 78 participants (27.3%) being men and 208 participants (72.7%) women between the ages of 18 and 34 (M = 22.1, SD = 2.79). Participants were requested to complete a demographic form, the Turkish version of the Mate Retention InventoryShort Form (MRI-SF), Rosenberg Self-Esteem Scale, and Multidimensional Jealousy Scale. Consistent with the earlier studies, the 19 mate retention tactics constituted a twocomponent structure. Sex differences in the adoption of mate retention strategies were investigated in order to assess the construct validity of the Turkish version of the MRI-SF. Additionally, the relationship between mate retention strategies and sexual jealousy and self-esteem was examined to determine the construct validity. The findings were in accordance with the previous studies and the analyses revealed that the Turkish MRI-SF is a valid measurement tool.
Keywords: Inventory; Short Form; Validity and Reliability; Turkish; Inventory; Short Form; Validity and Reliability; Turkish; Turkish; Inventory; Short Form; Validity and Reliability; Turkish; Turkish